Deubiquitinase Ubp5 is essential for pulmonary immune evasion and hematogenous dissemination of Cryptococcus neoformans - Guizhen Wang; Yan Liu; Qianyu Li; Changhui Wang; Wei Fang (Mycology)
The dynamic interplay between pathogens and host immune system determines the outcome of fungal infections. This study investigates the role of Ubp5 in modulating host defenses during Cryptococcus neoformans H99 infections. Ubp5 deletion significantly reduces both pulmonary invasion and extrapulmonary dissemination, resulting in prolonged survival and decreased fungal burdens in mice. Attenuated virulence is closely associated with enhanced host immune responses, rather than diminished pathogen fitness alone. Histopathological and leukocyte analyses revealed a shift towards protective adaptive immune responses in ubp5Δ-infected lungs, characterized by lymphocyte-dominated inflammatory infiltration and an increased Th1/Th17 cytokine response. Under host-associated conditions, ubp5Δ mutants exhibited morphological changes, including distorted shapes and cell wall heterogeneity, alongside defects in key virulence factors such as the polysaccharide capsule and melanin. These changes likely promote exposure of immunostimulatory cell wall components, enhancing host immunity. Additionally, Ubp5 deletion resulted in a significant reduction in intracellular ribosomal particles in C. neoformans, which likely impairs protein synthesis, contributing to reduced growth and pathogenic fitness in vivo. These findings underscore the pivotal role of Ubp5 in maintaining cryptococcal virulence and suggest that targeting Ubp5 could enhance host immunity against cryptococcosis by promoting protective immune responses and limiting fungal dissemination.